ANALISIS KINERJA KEUANGAN SEKTOR PERBANKAN SEBELUM DAN SESUDAH ADANYA PERUSAHAAN TEKNOLOGI FINANSIAL - Raysa Azahra Ade Putri (2021)
The goal of this study was to see if there was a difference in banks financial performance before and after the introduction of financial technology businesses, as measured by Profitability, Liquidity, and Capital. In this study, the population is banking sector enterprises registered on the Indonesia Stock Exchange (IDX). 152 sample units were acquired using the purposive sampling approach from 38 banks over a period of two years before the establishment of financial technology businesses (2013-2014) and two years after the existence of financial technology companies (2016-2017). With a 5% significance rate, the tests utilized in this study were Paired Sample T-test for normally distributed data and Wilcoxon Sign Rank Test for normally non-distributing data with spss 25 software assistance. After the existence of financial technology businesses, there is a difference in profitability as assessed by Return On Assets (ROA), liquidity as measured by loan to deposit ratio (LDR), and capital as measured by capital Adequacy Ratio (CAR).